Stitching through Silence: Walking With Our Sisters, Honoring the Missing and Murdered Aboriginal Women in Canada - Anderson, Stephanie G. (TEXTILE, 2016)
This article explores the complex relationship between processes of making, memory, healing, and social activism activated by Walking With Our Sisters, a large-scale commemorative installation intended to foster awareness for missing and murdered Indigenous women in Canada.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; art autochtone; art contemporain; artistes autochtones; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; féminicide; féminisme autochtone; histoire de l'art; histoire et politique; militance; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Poids - Carof, Solenne (Encyclopédie critique du genre, 2016)
Cette notice, en analysant comment le poids est à la fois le réceptacle de différentes normes et représentations sociales, mais également l’objet de revendications et de résistances, s’inscrit pleinement dans les thématiques des études sur le genre. Le poids permet, en effet, de saisir aussi bien les rapports sociaux révélés dans la prégnance de certaines normes corporelles - la minceur par exemple - que l’interdépendance de ces normes sociales avec d’autres rapports de domination. Être désigné comme « normal » ou « obèse », au-delà de l’historicité et des controverses entourant ces catégorisations, n’a pas le même sens selon les caractéristiques sociales des individus et peut reconfigurer les rapports sociaux existants.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; corps; cours; discipline; europe; france; grossophobie; inégalités; matérialité; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; violences

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
https://uqam-bib.on.worldcat.org/oclc/953804743
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Conceptualizing Pornographication: A Lack of Clarity and Problems for Feminist Analysis - Tyler, Meagan; Quek, Kaye (Sexualization, Media, & Society, 2016)
The mainstreaming of pornography, often referred to as pornographication, pornification, or porn-chic, has become a topic of considerable academic and popular interest. In the last 15 years, an expanding academic literature has documented and begun to analyze the increasing consumption and normalization of pornography as well as pornographic imagery. More recently, there has also been a growing concern among policymakers and commentators in the mainstream media about trends labeled “sexualization” and, in particular, the potential consequences of these trends for children. This article begins by sketching out the academic origins of “pornographication” and related terms before considering the different ways that prominent authors have conceptualized them. Recent literature on sexualization is then outlined, with a focus on understanding this in the context of discussions around pornographication. Using a number of examples from key academic texts, and from prominent print media outlets in Australia, we argue that there is a lack of conceptual clarity about pornographication and that pornographication is often conflated with sexualization. We suggest that the lack of clarity in existing literature creates two key issues for feminist analysis: (1) it obscures the role of the pornography industry in the processes of pornographication and (2) it deflects discussion away from the potential harms of the normalization of pornography and pornographic imagery for adult women. It is, therefore, important to clarify and separate the terminology of pornographication and sexualization in order to further critical feminist analyses of these cultural trends.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; discours dominant; pornographie; premier cycle; périodes historiques; sciences humaines; sciences sociales; sex1911; sexualité; systèmes d'oppressions; thématiques; violences